Covalent non-fused tetrathiafulvalene–acceptor systems. Issue 51 (19th May 2016) - Pop, Flavia; Avarvari, Narcis
Abstract : The main families of non-fused TTF–acceptors are discussed with a special focus on their characteristics and properties. Abstract : Covalent donor–acceptor (D–A) systems have significantly contributed to the development of many organic materials and to molecular electronics. Tetrathiafulvalene (TTF) represents one of the most widely studied donor precursors and has been incorporated into the structure of many D–A derivatives with the objective of obtaining redox control and modulation of the intramolecular charge transfer (ICT), in order to address switchable emissive systems and to take advantage of its propensity to form regular stacks in the solid state. In this review, we focus on the main families of non-fused TTF–acceptors, which are classified according to the nature of the acceptor: nitrogen-containing heterocycles, BODIPY, perylenes and electron poor unsaturated hydrocarbons, as well as radical acceptors. We describe herein the most representative members of each family with a brief mention of their synthesis and a special focus on their D–A characteristics. Special attention is given to ICT and its modulation, fluorescence quenching and switching, photoconductivity, bistability and spin distribution by discussing and comparing spectroscopic and electrochemical features, photophysical properties, solid-state properties and theoretical calculations.